Dietary Rice Bran Plays A Significant Role in the Hepatoprotective Effect in Hypercholesterolemic Rats - Antula, Yulianti; Neno, Dolly Irnawati; Srihardyastutie, Arie; Mahdi, Chanif (The Journal of Experimental Life Science, 2019)
Cholesterol is obtained through biosynthesis and diet. When a level of cholesterol is above the normal level, this condition caused hypercholesterolemia. Long-term administration of synthetic chemical drugs can cause liver damage. Therefore, alternative natural medication is needed. One of the alternatives that can be used is the rice bran (RB), which contains antioxidant and crude fiber. This study is aimed at finding out the potential utilization of RB on total cholesterol level, liver enzyme as aspartate aminotransferase (AST) and alanine aminotransferase (ALT), malondialdehyde (MDA), and the changes in liver tissue. This study uses five groups of rats: the negative control group, positive control group, and three therapy groups with the dosage of 270 mg kg-1, 540 mg kg-1, and 810 mg kg-1 of body weight. This study shows that therapy using RB can significantly decrease the cholesterol level, AST, ALT, and MDA (p<0.01). The total cholesterol level is 21%, AST and ALT activities can be reduced to 54% and 64%, the level of MDA reduced to 79% and can repair the liver tissue. This study shows that RB can be effectively used as hepatoprotective in rats with hypercholesterolemia. Keywords: AST and ALT, Hypercholesterolemia, Rice Bran, Total Cholesterol Level.